Genomics: A potential panacea for the perennial problem1. Issue 10 (1st October 2014) - McClure, Kendra A.; Sawler, Jason; Gardner, Kyle M.; Money, Daniel; Myles, Sean
Abstract : Perennial crops represent important fresh and processed food sources worldwide, but advancements in breeding perennials are often impeded due to their very nature. The perennial crops we rely on most for food take several years to reach production maturity and require large spaces to grow, which make breeding new cultivars costly compared with most annual crops. Because breeding perennials is inefficient and expensive, they are often grown in monocultures consisting of small numbers of elite cultivars that are vegetatively propagated for decades or even centuries. This practice puts many perennial crops at risk for calamity since they remain stationary in the face of evolving pest and disease pressures. Although there is tremendous genetic diversity available to them, perennial crop breeders often struggle to generate commercially successful cultivars in a timely and cost‐effective manner because of the high costs of breeding. Moreover, consumers often expect the same cultivars to be available indefinitely, and there is often little or no incentive for growers and retailers to take the risk of adopting new cultivars. While genomics studies linking DNA variants to commercially important traits have been performed in diverse perennial crops, the translation of these studies into accelerated breeding of improved cultivars has been limited. Here we explain the "perennial problem" in detail and demonstrate how modern genomics tools can significantly improve the cost effectiveness of breeding perennial crops and thereby prevent crucial food sources from succumbing to the perils of perpetual propagation.